FORMULATION AND ACTIVITY TESTS OF ANTI-ACNE TONER ESSENTIAL OIL OF RED BETEL LEAF (Piper crocatum) - Riska Permata, Bangkit; Jayak Pratama, Kharisma; Nurul Kotimah, Mei Ika (LPPM Universitas Duta Bangsa Surakarta, 2023)
Red betel leaf (Piper crocatum) is a plant that can be used as an antibacterial. Red betel leaves contain flavonoids, alkaloids, tannins, and essential oils which are thought to be used as antimicrobials. The purpose of this study was to determine the antibacterial activity of red betel leaf (Piper crocatum) essential oil facial toner as an anti-acne toner against Propionibacterium acnes bacteria. Red betel leaf is distilled to obtain essential oil, then tested for organoleptic, specific gravity, pH, viscosity, solubility in alcohol. Making facial toner preparations using concentrations of 10%, 20% and 30%. The results of the formula were then subjected to physical quality tests including organoleptic tests, pH tests, viscosity, anti-irritation tests, hedonic tests and activity tests against Propionibacterium acnes bacteria. Toner preparation activity test results obtained concentrations of 10% 9.2 mm, 20% 11.26 mm, 30% 13.46 mm. Red betel leaf essential oil toner can inhibit the growth of Propionibacterium acnes bacteria with the highest concentration of 30% obtained inhibition of 13.46 mm in the strong category.